Patients' and carers' preferences in two models of care for acute exacerbations of COPD: results of a randomised controlled trial. Issue 2 (1st February 2002) - Ojoo, J C; Moon, T; McGlone, S; Martin, K; Gardiner, E D; Greenstone, M A; Morice, A H
Abstract : Background: Patients with an acute exacerbation of chronic obstructive pulmonary disease (COPD) were randomised to either hospital at home (HaH) or inpatient management, and patient and carer preferred site of management and satisfaction with care received in the two arms was determined. Methods: Emergency admissions with an acute exacerbation of COPD were randomised to inpatient care or HaH care. After discharge an independent observer administered a questionnaire to both patients and carers on the preferred site of care and scored satisfaction with the care received. Results: Of 60 patients recruited, 30 were randomised to receive HaH care. Retrospective patient preference for HaH care was 96.3% in the domiciliary arm and 59.3% in the conventional arm; carer preference figures were 85.7% and 42.9%, respectively. There was a higher preference for domiciliary care by both patients and carers in the HaH arm than in the inpatient arm (p=0.001 and p=0.01, respectively). Patients recorded equal satisfaction with care in the two arms (88.1% in the conventional arm, 91.7% in the domiciliary arm); carer scores were 91.3% and 91.9%, respectively. Conclusions: The results of this study show that both patients and carers were significantly more likely to prefer domiciliary care if they were in the HaH arm. Since patients had to be willing to be looked after at home, both patients' and carers' perceptions of the benefits of HaH care were reinforced by their experience. HaH care of acute exacerbations of COPD is the preferred option in suitable patients.